Kaposiform haemangioendothelioma in an adult: lack of response to topical sirolimus and response to radiotherapy. (22nd September 2021) - Der Sarkissian, S. A.; Wong, X. L.; Kossard, S.; Hong, A.; Sebaratnam, D. F.
Abstract : Kaposiform haemangioendothelioma (KHE) is a rare, primarily paediatric tumour with only a handful of case reports in the adult population. Given the paucity of evidence, this article is important in raising awareness of radiotherapy as a suitable and effective treatment in the adult population with KHE and highlights the potential limitations of topical sirolimus in these tumours.